2014
DOI: 10.3109/00016489.2014.913314
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic therapy of fosaprepitant, palonosetron, and dexamethasone combined with cisplatin-based chemotherapy for head and neck carcinomas

Abstract: The frequency of the primary end point of complete response in the overall phase was 69.0%. The proportion of patients with no vomiting in the overall phase was 90.1%. In the acute phase, the proportion of no nausea and slight nausea together was 91.5%, no change in and slightly reduced food intake together was 87.3%, and the proportion of good general condition and relatively good general condition was 85.9%. In the delayed phase, the proportion of no nausea and slight nausea together was 56.3%, no change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…As previously reported, in the cisplatin stratum (Table 2), delayed-phase CR was numerically higher in the APF530 arm versus the ondansetron arm, with a corresponding treatment difference of 10 18 This more in-depth analysis found similar trends favoring the APF530 over the ondansetron regimen across overalland acute-phase CR (Table 2).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As previously reported, in the cisplatin stratum (Table 2), delayed-phase CR was numerically higher in the APF530 arm versus the ondansetron arm, with a corresponding treatment difference of 10 18 This more in-depth analysis found similar trends favoring the APF530 over the ondansetron regimen across overalland acute-phase CR (Table 2).…”
Section: Resultssupporting
confidence: 80%
“…8,9 However, the administration of oral medication to patients experiencing CINV and those with head and neck cancer may be difficult. 10 Alternative antiemetic treatments that provide CINV control into the delayed phase and with a convenient route of administration, are needed.…”
mentioning
confidence: 99%
“…While a three-day oral regimen of aprepitant was the first approved NK 1 RA, randomized controlled trials have shown that a single IV dose of fosaprepitant is non-inferior to aprepitant and may be more convenient for patients. 4,5 According to the National Comprehensive Cancer Network antiemetic guidelines, 2 the addition of an NK 1 RA to dexamethasone and a 5HT-3 RA is an effective combination for relieving CINV due to highly and some moderately emetogenic chemotherapy. The most common adverse reactions reported for fosaprepitant are fatigue, diarrhea, neutropenia, asthenia, anemia, peripheral neuropathy, leukopenia, dyspepsia, urinary tract infection, and pain in the extremity.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear, however, whether palonosetron is more effective against delayed emesis when administered with an NK 1 RA. Several single-arm studies found that palonosetron had additional antiemetic efficacy when added to aprepitant and dexamethasone in patients with gynecological, head/neck and lung cancer [ 29 31 ]. Only one phase III trial, the TRIPLE study, compared granisetron and palonosetron added to basal antiemetic therapy with NK 1 RA and corticosteroid, finding that palonosetron was superior to granisetron in preventing delayed emesis and nausea [ 32 ].…”
Section: Discussionmentioning
confidence: 99%